News in antimicrobial therapy. Part III – anaerobes, Gramnegative baccili and “atypical” pathogens - Drzewiecki, Artur; Bulanda, Małgorzata (Przewodnik Lekarza/Guide for GPs, 2005)
In this part we have described news in antimicrobial therapy concerning Gramnegative baccili, anaerobes and “atypical” pathogens.